The Effect of Profitability and Company Size on Tax Avoidance in the Mining Sector Listed on the IDX in 2019-2023 - Septania Indri Ariyani; Muhammad Iqbal (Jurnal Riset Perpajakan: Amnesty, 2025)
This study investigates the effect of profitability and company size on tax avoidance in mining sector companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Tax avoidance remains a critical issue in the mining industry due to its strategic contribution to state revenue and the sector’s vulnerability to aggressive tax practices. Using a purposive sampling method, 10 mining companies meeting the research criteria were selected, resulting in 50 firm-year observations. The study employs multiple linear regression analysis using IBM SPSS Version 29 to assess the relationship among variables. The classical assumption tests—normality, multicollinearity, heteroscedasticity, and autocorrelation—confirmed the validity of the regression model. The findings reveal that profitability has no significant effect on tax avoidance, indicating that highly profitable companies tend to comply with tax regulations to avoid reputational and legal risks. Conversely, company size shows a significant positive effect on tax avoidance, suggesting that larger firms possess greater resources and access to professional expertise, enabling them to implement structured tax avoidance strategies. The model’s Adjusted R² value of 0.181 indicates that 18.1% of tax avoidance behavior can be explained by profitability and company size. The study contributes to tax management literature by providing empirical evidence on firm characteristics influencing tax avoidance in Indonesia’s mining industry and offers insights for policymakers to enhance regulatory oversight.